Synthesis and characterization of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages - Pal, R. R.; Patil, P. S.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Polymer International, 2005)
A series of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages was synthesized from two new diacids, namely 2,4-bis-(4-carboxyphenoxy)-6-thiophenoxy-s-triazine and 2,4-bis-(3-carboxyphenoxy)-6-thiophenoxy-s-triazine, and commercially available aromatic diamines by using Yamazaki's phosphorylation reaction. The polyamides were obtained in good yields and were characterized by solubility tests, viscosity measurements, FTIR, H-1 and C-13 NMR spectroscopy, X-ray diffraction studies and thermogravimetric analysis. The polyamides were found to have inherent viscosities in the range of 0.35 to 0.56 dl g(-1) in N,N-dimethylacetamide (DMAc) at 30 +/- 0.1 degreesC. All the polyamides were readily soluble in solvents such as DMAc, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) and m-cresol. Thermogravimetric analysis of the polyamides indicated no weight loss below 345 degreesC under a nitrogen atmosphere. (C) 2004 Society of Chemical Industry.
Keywords: 2; 4-bis-(3/4-carboxyphenoxy)-6-thiophenoxy-s-triazine; direct polycondensation; polyamide; s-triazine ring